Nowe dwudziestolecie (1989–2009). Rozpoznania, hierarchie, perspektywy [The New Twenties (1989-2009): Recognitions, Hierarchies, Perspectives]. Ed. by Hanna Gosk. Warsaw: Dom Wydawniczy Elipsa, p. 530, ISBN 978-83-7151-873-7 - Németh, Orsolya (Slavica, 2023)
The volume Nowe dwudziestolecie (1989-2009): Rozpoznania, hierarchie, perspektywy [The new twenties (1989-2009): Recognitions, hierarchies, perspectives] reflects on the twenty years of Polish literature and literary change between 1989 and 2009, and compares and contrasts this period with the twenty years between the two world wars. The two twenty-year periods are linked by the fact that their starting point is associated with a date of immense importance for Polish history: 1918 is the year when Poland was returned on the map of Europe, and 1989 is also the year of the change of regime in Poland. The period between the two world wars is also regarded as a separate period in Polish literary history, while the second twenty years covered in this volume are questionable as a literary unit, a question which the essays in this book seek to answer. The volume is divided into three large sections, the first focusing primarily on theory, the second on Polish characteristics and themes that characterised Polish literature after 1989, and the third large section on the genre characteristics that have characterised Polish literature since the fall of communism to this day but were also important between the two world wars.